2015
DOI: 10.3144/expresspolymlett.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline polymer nanocomposites reinforced with in-situ reduced graphene oxide

Abstract: Abstract. In this work liquid-crystalline polymer (LCP) nanocomposites reinforced with in-situ reduced graphene oxide are investigated. Graphene oxide (GO) was first synthesized by the Hummers method, and the kinetics of its thermal reduction was assessed. GO layers were then homogeneously dispersed in a thermotropic liquid crystalline polymer matrix (Vectran ® ), and an in-situ thermal reduction of GO into reduced graphene oxide (rGO) was performed. Even at low rGO amount, the resulting nanocomposites exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…Thermal reduction of GO seemed to be an easy and effective route to develop graphene based nanocomposites, but elevated temperatures (from 300°C to 1,000°C) are generally required to achieve a satisfactory GO reduction . This is the reason why this process generally requires polymers with elevated thermal stability , like liquid‐crystalline polymers (LCP) .…”
Section: Introductionmentioning
confidence: 99%
“…Thermal reduction of GO seemed to be an easy and effective route to develop graphene based nanocomposites, but elevated temperatures (from 300°C to 1,000°C) are generally required to achieve a satisfactory GO reduction . This is the reason why this process generally requires polymers with elevated thermal stability , like liquid‐crystalline polymers (LCP) .…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding mechanical and conductive properties of carbon nanoparticles (CNPs), together with their unique structure and low density, place them among the most common fillers. Carbon nanofiber and carbon nanotubes (CNT) [14][15][16][17][18][19][20] 1,2 , N. Miklósi 1 and its derivatives [21][22][23][24], mainly graphene oxide (GO), have attracted marked interest in the last few years. In biomedical applications, however, the uncertainty surrounding the toxicity of CNTs [14] could affect choices of nanocarbon filler.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mechanical and electrical property enhancement was found in graphene nanoplatelet/LCP nanocomposites . Finally, regarding effects on molecular dynamics, Pedrazzoli et al reported in a recent publication that in situ reduced graphene oxide had no effects on the secondary γ and β relaxations studied by dynamic mechanical analysis (DMA) in a thermotropic MCLCP, Vectran ® , whereas the segmental α relaxation became slightly slower ( T g shifting by 4°C to higher temperatures on addition of 3 wt% graphene oxide).…”
Section: Introductionmentioning
confidence: 99%